SWOT analysis of the usability of augmented and virtual reality in teaching crisis management - Smetana, Marek; Kavan, Štěpán; Tomanová, Kateřina (Vysoká škola bezpečnostného manažérstva v Košiciach, 2020)
The paper focuses on determining the main possibilities and benefits of using augmented and virtual reality in teaching university students in the field of crisis management. One of the basic problems of future members of crisis staff, who will coordinate the solution of the most extensive events with the most serious impacts, is the inability to try the solution in advance with the possibility of finding the most effective variant. The aim of the paper is to show that with the help of simulations this problem can be eliminated. At the same time, the paper contains a definition of the main obstacles and limitations that accompany the use of simulations.
SWOT analýza využitelnosti rozšířené a virtuální reality při výuce krizového řízení
Keywords: Simulation; augmented reality; virtual reality; crisis management; crisis staffs; simulace; rozšířená realita; virtuální realita; krizové řízení; krizové štáby